Severe congenital lipodystrophy and a progeroid appearance: Mutation in the penultimate exon of FBN1 causing a recognizable phenotype. Issue 12 (16th August 2013) - Takenouchi, Toshiki; Hida, Mariko; Sakamoto, Yoshiaki; Torii, Chiharu; Kosaki, Rika; Takahashi, Takao; Kosaki, Kenjiro
Abstract Recently, three marfanoid patients with congenital lipodystrophy and a neonatal progeroid appearance were reported. Although their phenotype was distinct from that of classic Marfan syndrome, they all had a truncating mutation in the penultimate exon, i.e., exon 64, of FBN1, the causative gene for Marfan syndrome. These patients might represent a new entity, but the exact phenotypic and genotypic spectrum remains unknown. Here, we report on a girl born prematurely who exhibited severe congenital lipodystrophy and a neonatal progeroid appearance. The patient exhibited a characteristic growth pattern consisting of an accelerated growth in height with a discrepant poor weight gain. She had a characteristic facial appearance with craniosynostosis. A mutation analysis identified c.8175_8182del8bp, p.Arg2726Glufs*9 in exon 64 of the FBN1 gene. A review of similar, recently reported patients revealed that the cardinal features of these patients include (1) congenital lipodystrophy, (2) premature birth with an accelerated linear growth disproportionate to the weight gain, and (3) a progeroid appearance with distinct facial features. Lines of molecular evidence suggested that this new progeroid syndrome represents a neomorphic phenotype caused by truncated transcripts with an extremely charged protein motif that escapes from nonsense‐mediated mRNA decay, altering FBN1‐TGF beta signaling, rather than representing the severe end of the hypomorphic phenotype of the FBN1‐TGF beta disorder spectrum. We propose that this marfanoid entity comprised of congenital lipodystrophy, a neonatal progeroid appearance, and a peculiar growth profile and caused by rare mutations in the penultimate exon of FBN1, be newly referred to as marfanoid–progeroid syndrome. © 2013 Wiley Periodicals, Inc.